2012
DOI: 10.7841/ksbbj.2012.27.5.289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol on Migration and Proliferation in HT-29 Colon Cancer Cells

Abstract: 1) Resveratrol, natural polyphenol in grapes and red wine, is known to have the anti-proliferatory and anti-angiogenic effects in various cancer cells. In this study, we have investigated the effects of resveratrol in HT-29 colon cancer cells. Treatment of resveratrol in different concentrations and time inhibited proliferation of HT-29 colon cancer cells. We explored the effects of resveratrol on HT-29 colon cancer cell motility using a wound healing assay. In the absence of the resveratrol, the HT-29 cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Cancer is caused by the abnormal proliferation of cells, and interference with cell proliferation as well as induction of cancer cell death have been widely employed in the treatment of cancer (6). Colon cancer is of particular interest in South Korea, as its prevalence has increased with the adaptation of Western eating habits (1,2). Previous studies have shown that various plant extracts have anti-cancer effects and cause apoptosis of HCT116 colon cancer cells (4,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer is caused by the abnormal proliferation of cells, and interference with cell proliferation as well as induction of cancer cell death have been widely employed in the treatment of cancer (6). Colon cancer is of particular interest in South Korea, as its prevalence has increased with the adaptation of Western eating habits (1,2). Previous studies have shown that various plant extracts have anti-cancer effects and cause apoptosis of HCT116 colon cancer cells (4,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…results indicated that CME exerts cytotoxic effects and induces apoptosis via the downregulation of Akt. p-AMPK and p-Akt are upstream regulators that trigger apoptosis through modulation of individual signaling pathways (2,12). To investigate whether CME downregulates Akt through the activation of AMPK or through direct inhibition, signaling proteins associated with AMPK-and Akt-mediated apoptosis were assessed after treatment CME alone or following pre-treatment with AMPK and Akt inhibitors.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…대장암은 전 세계적으로 발병률이 높은 악성종양 중의 하나 로, 국내에서도 서구화된 식습관으로 인하여 매년 증가하고 있다 [21,25,27]. 대장암은 주로 암을 절제하는 외과적 수술로 치료가 이루어지며, 암의 병기(staging)에 따라 항암제 또는 방사선치료가 병행된다.…”
Section: 서 론unclassified